Evaluation of a peer counselling programme to sustain breastfeeding practice in Hong Kong - Choi Kai-Chow; Nelson EAS; Wong Esther HY; Wong Kin-Ping; Ip Carmen; Ho Lau-Cheung (BMC, 2007)
Abstract Background Peer counselling is reported to increase breastfeeding rates. We evaluated an intervention consisting of mainly telephone contact peer counselling programme on breastfeeding duration and exclusivity. Methods Peer counsellors (PCs) were mothers who had successfully breastfed and had received formal training. Following a postnatal visit, they provided scheduled telephone consultations (Days 1, 4, 7, Weeks 2, 4, 8, and Month 4) to PC group mothers (n = 100) who continued breastfeeding their infants after discharge. Control group mothers (n = 100) received routine care. Results After adjusting for mothers' previous breastfeeding experiences, mothers' working status and breastfeeding problems, no statistical differences in mothers' feeding methods (exclusive, almost exclusive or predominant breastfeeding) were noted at the three follow-up times for intervention and control mothers respectively (Day 5: 37%/38%, 46%/53%, 57%/63%; Month 3: 10%/9%, 17%/23%, 20%/26%; Month 6: 2%/1%, 18%/18%, 18%/19%). All differences between the groups were not significant. Also, there was no evidence to suggest that PC intervention prolonged breastfeeding duration. Conclusion The lack of effect of our PC intervention may reflect the low baseline breastfeeding rate and low value placed on breastfeeding in our population, the type of PC intervention or group allocation biases. Trial registration ISRCTN93605280.